Modulating the anti-cancer photodynamic efficiency of molybdenum-iodide nanoclusters via ligand design - Přibyl, Tomáš; Škoch, Karel; Bavol, Dmytro; Křížová, Ivana; Zelenka, Jaroslav; Ruml, Tomáš; Lang, Kamil; Kirakci, Kaplan (Journal of materials chemistry. B, 2025)
Ligand-stabilized metallic nanoclusters are emerging as promising agents for photodynamic therapy (PDT). This study explores how precisely tailored ligands can optimize the anti-cancer PDT efficiency of molybdenum-iodide nanoclusters. Utilizing click chemistry, we synthesized a series of triazolate-capped nanoclusters by reacting Na2[Mo6I8(N3)6] with dibenzo[a,e]cyclooctyne (DBCO) derivatives. Dynamic light scattering and luminescence measurements confirmed that the bulky DBCO moieties effectively stabilized the nanoclusters in aqueous media, while the appended side chains dictated their colloidal behavior and photosensitizing capabilities. In vitro experiments with HeLa cancer cells revealed that the side chain's nature critically influences cellular uptake and phototoxicity. Positively charged nanoclusters exhibited enhanced cell membrane interactions and potent phototoxic effects, whereas negatively charged counterparts displayed reduced internalization and diminished PDT efficacy. Notably, the nanoclusters maintained consistent phototoxicity even after prolonged exposure to aqueous media, demonstrating the robust stability conferred by the DBCO ligands. These results higlight the potential for fine-tuning molybdenum-iodide nanocluster properties to optimize PDT applications, achieving a delicate balance between water stability, cellular interaction, and phototoxicity, thereby isolating key parameters that govern PDT efficiency.
Keywords: jodidy; Humans; fotosenzibilizující látky; Molecular Structure; Particle Size; Antineoplastic Agents; molybden; HeLa buňky; Photochemotherapy; protinádorové látky; Drug Screening Assays, Antitumor; Ligands; screeningové testy protinádorových léčiv; Iodides; Cell Survival; viabilita buněk; ligandy; velikost částic; Photosensitizing Agents; HeLa Cells; lidé; fotochemoterapie; Molybdenum; molekulární struktura